Comparative Assessment of Pathological Condition of Selected Mahogani Trees (2014)
Sustainability of mahogany trees have been threatened by the pandemic of fungal diseases, but Variation exists in the level of occurrence of the diseases among the trees. Thus, diagnosing the level of susceptibility of mahogany to the diseases will be the first step to ameliorating the impact of the diseases on the trees' abundance. This study comparatively investigated the pathological status of selected mahogany trees (Khaya senegalensis and Entandrophfagma cylindricum. Diseased samples of the tree species were collected from a mahogany forest located in Ijebu-Ode, Ogun State, Nigeria. Data were collected through laboratory analysis of the samples and statistically analyzed with the use of ANOVA and t-test at cto.os. Result shows that £. cylindricum is more susceptible to fungal attack by collectotrichum (66.67%), aspergillus (22.22%) and fusarium (18.51%). While in K. senegalensis, the frequency of occurrence (FOC) of the diseases were 62.96%, 14.81% and 14.81% respectively. There was however, no significant different in the FOC of the two species. ßut on utility, it is better tö adhere to K. senegalensis:it has less pathological weakness